2015
DOI: 10.1377/hlthaff.2015.0536
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionate Impact Of Dementia On Family And Unpaid Caregiving To Older Adults

Abstract: The number of US adults ages sixty-five and older who are living with dementia is substantial and expected to grow, raising concerns about the demands that will be placed on family members and other unpaid caregivers. We used data from the 2011 National Health and Aging Trends Study and its companion study, the National Study of Caregiving, to investigate the role of dementia in caregiving. We found that among family and unpaid caregivers to older noninstitutionalized adults, one-third of caregivers, and 41 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
339
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 302 publications
(347 citation statements)
references
References 22 publications
7
339
0
1
Order By: Relevance
“…26,27 Our study extends existing evidence that has established the special challenges encountered by caregivers of persons with dementia. 15,28,29 We found that almost half of the caregivers providing substantial help with health care activities assist an older adult with dementia. For the first time to date, we also quantify the emotional, financial, physical, participation, and work-related effects of caregiving experienced by family caregivers who interact with health care professionals and manage health care activities on behalf of or alongside older adults.…”
Section: Discussionmentioning
confidence: 83%
“…26,27 Our study extends existing evidence that has established the special challenges encountered by caregivers of persons with dementia. 15,28,29 We found that almost half of the caregivers providing substantial help with health care activities assist an older adult with dementia. For the first time to date, we also quantify the emotional, financial, physical, participation, and work-related effects of caregiving experienced by family caregivers who interact with health care professionals and manage health care activities on behalf of or alongside older adults.…”
Section: Discussionmentioning
confidence: 83%
“…Dementia caregivers reported a striking degree of physical difficulty regardless of older adults’ survival status, which corresponds with extraordinarily high care needs of advanced dementia 37 and the physical toll associated with sleep interruptions, managing burdensome symptoms, and complete assistance with self-care activities. 38 The finding that financial difficulty was significantly higher among EOL cancer caregivers is notable in light of growing recognition and concern regarding the high costs of cancer care, 39 which may extend beyond patients to their families.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that total health and long-term care costs for persons with Alzheimer’s and other dementias in the United States will total $259 billion in 2017, more than two thirds of which is expected to be covered by public sources such as Medicare and Medicaid ( 2 ). Additionally, most care provided to older adults with Alzheimer’s who do not live in long-term care facilities is provided by family members or other unpaid caregivers ( 7 ). In 2015, caregivers of persons with dementia, including Alzheimer’s, provided 18.2 billion hours of unpaid assistance ( 2 ).…”
Section: Discussionmentioning
confidence: 99%